Predictors of mortality among adult patients enrolled on Antiretroviral Therapy in Hiwotfana specialized University Hospital, Eastern Ethiopia: Retrospective Cohort study - Endalkachew Mekonnen Eticha; Ashenafi Beru Gemeda (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2018)
Objective: Mortality of Human Immunodeficiency Virus (HIV)- infected patients have been reduced substantially since the introduction of Antiretroviral Therapy (ART). However, many studies have shown high mortality. But the factors associated with this high mortality are poorly characterized. So this retrospective cohort study aims to determine mortality and identify predictors of it among patients on ART at Hiwotfana specialized university Hospital (HFSUH). Result: A total of 61 (11.9%) deaths were observed giving an overall mortality rate of 2.8 per 100 person years. Advanced WHO stages (hazard ratio (HR) =3.44, 95% CI: 1.73 - 6.85), baseline CD4 count less than 200cells/mm3 (HR=3.18, 955 CI: 1.671- 6.06), regimen changed (HR=23.62, 95% CI: 9.95 - 56.05), and being anemic (HR=3.23, 95% CI: 1.71 - 6.11) were the independent predictors of mortality. Patients who started AZT based initial regimen had a lower risk of mortality (HR=0.29, 95% CI=0.13 - 0.64) when compared with the D4T based regimen.